A systematic review for the development of Alzheimer’s disease in in vitro models: a focus on different inducing agents - Prajapat, Manisha; Kaur, Gurjeet; Choudhary, Gajendra; Pahwa, Paras; Bansal, Seema; Joshi, Rupa; Batra, Gitika; Mishra, Abhishek; Singla, Rubal; Kaur, Harminder; Prabha, Praisy K.; Patel, Ajay Prakash; et al. (Frontiers in Aging Neuroscience, 2023)
Alzheimer's disease (AD) is the most common progressive neurodegenerative disease and associated with dementia. Presently, various chemical & environmental agents are used to induce in-vitro models of Alzheimer disease to investigate the efficacy of different therapeutic drugs. We screened literatures from database like PubMed, ScienceDirect & Google scholar emphasizing the diverse targeting mechanisms of neuro degeneration explored in in-vitro models. The results showed studies in which different types of chemicals and environmental agents were used for in-vitro development of Alzheimer targeting mechanisms of neurodegeneration. The studies with chemically induced in-vitro AD modelsincluded in systematic review will contribute to deeper understanding of AD. However, none of these models can reproduce all the characteristics of disease progression seen in majority of Alzheimer's disease subtypes. Additional modifications would be required to replicate the complex conditions of human AD in an exact manner. In-vitro models of Alzheimer's disease developed using chemicals and environmental agents are instrumental in providing insights into the disease's pathophysiology, therefore chemical-induced in-vitro AD models will continue to play vital role in future AD research. This systematic screening revealed the pivotal role of chemical-induced in-vitro AD models in advancing our understanding of AD pathophysiology and therefore important to understand the potential of these chemicals in AD pathogenesis.